CP-171 Biological drugs: persistence rate in patients with rheumatoid arthritis and spondylarthritis. (25th February 2017) - Santoro, M; Semeraro, A; Giglio, G; Digiuseppe, F; Mingolla, G; Cannarile, G; Castellana, M; D'Aprile, L
Abstract : Background: Rheumatic diseases, such as rheumatoid arthritis and spondylarthritis, are chronic autoimmune diseases that can be treated with new biological drugs. Purpose: The purpose of this study was to evaluate drug retention as a surrogate for the effectiveness of biologic therapy. Material and methods: In a rheumatological centre in Apulia, Italy, 210 patients with rheumatoid arthritis (RA) and 336 patients with spondylarthritis (SpA) were evaluated, following treatment with 'biologics' from 1 January 2001 to 31 May 2016. The effectiveness of the biological drugs was evaluated using Kaplan–Meier drug retention curves. Results: For RA patients, we analysed data after 2, 4 and 5 years of therapy. At 2 years, the drug persistence rates were: 75% for etanercept, 63% for rituximab, 60% for adalimumab, 50% for abatacept with a rapid decrease during continuation of therapy; and 42% for infliximab at 2 years and 25% at 4 years. At 5 years the values were: 57% for tocilizumab and 35% for rituximab, adalimumab, etanercept and certolizumab. For SpA patients, we analysed the data after 2 and 4 years of therapy. At 2 years, the drug persistence rates were: 50–56% for etanercept, infliximab and adalimimab, 35% for certolizumab and 31% for golimumab. Ustekinumab was not statistically evaluable because marketing authorisation was less than 2 years. At 4 years the values were: 44% for etanercept, 38% for adalimumab, 34% for infliximab and 13% for golimumab. Certolizumab was not statistically evaluable because it was commercially available for less than 4 years for psoriatic arthritis. Conclusion: A comparison of RA and SpA showed that RA patients had a higher persistence after 2 years of treatment (75–60% vs 55–50%) than SpA patients; at 4 years the drug persistence rate was 50% for RA compared with 35% for SpA. In this study, RA patients probably responded better to 'biological drugs' because the biological targets were defined; in SpA, targets are less known, having recently discovered the IL-23/IL-17 (interleukin-23/interleukin-17) aetiopathogenetic way. Therefore, the different clinical responses and frequent change in drugs shows that it cannot predict either therapeutic response or appearance of adverse events. References and/or acknowledgements: We would like to thank the UO of Rheumatology at ASL Taranto and pharmacists at the Hospital Pharmacy of ASL Taranto No conflict of interest